2019
DOI: 10.3390/ijms20040837
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Stress-Inducible SsMAX2 Promotes Drought and Salt Resistance via the Regulation of Redox Homeostasis in Arabidopsis

Abstract: Recent studies have demonstrated that strigolactones (SLs) also participate in the regulation of stress adaptation; however, the regulatory mechanism remains elusive. In this study, the homolog of More Axillary Branches 2, which encodes a key component in SL signaling, in the perennial oil plant Sapium sebiferum was identified and functionally characterized in Arabidopsis. The results showed that the expression of SsMAX2 in S. sebiferum seedlings was stress-responsive, and SsMAX2 overexpression (OE) in Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…rty expression promotes drought stress responses via ABA-regulated stomatal closure Plant drought responses involve a complex process regulated by multiple molecular and cellular pathways. The expression levels of some genes are upregulated or downregulated by exposure to abiotic stresses, and the heterologous expression of these genes can increase the tolerance of transgenic plants to drought or salt stress [48][49][50][51]. Consistent with this, our results indicated that the eheterologous expression of rty has critical effects on strawberry drought responses.…”
Section: Heterologous Expression Of Rty Increases the Drought Toleransupporting
confidence: 83%
“…rty expression promotes drought stress responses via ABA-regulated stomatal closure Plant drought responses involve a complex process regulated by multiple molecular and cellular pathways. The expression levels of some genes are upregulated or downregulated by exposure to abiotic stresses, and the heterologous expression of these genes can increase the tolerance of transgenic plants to drought or salt stress [48][49][50][51]. Consistent with this, our results indicated that the eheterologous expression of rty has critical effects on strawberry drought responses.…”
Section: Heterologous Expression Of Rty Increases the Drought Toleransupporting
confidence: 83%
“…The homolog of More Axillary Branches 2 ( MAX2 ) encodes for a key component in the strigolactones (SL) signalling pathway. The overexpression of MAX2 from Sapium sebiferum ( SsMAX2 ) in Arabidopsis plants significantly promoted resistance to different abiotic stresses (drought, osmotic, and salinity) [9]. The authors showed that the protein MAX2 potentially influences chlorophyll metabolism, anthocyanin biosynthesis, soluble sugars, and proline accumulation.…”
Section: Transgenic Strategymentioning
confidence: 99%
“…The physiological and biochemical analyses demonstrated that SsMAX2 plays a pivotal role in the regulation of redox homeostasis via the regulation of antioxidative enzymes. In this sense, a potential interaction between SL and abscisic acid (ABA) in the adaptation to abiotic was suggested [9].…”
Section: Transgenic Strategymentioning
confidence: 99%
“…Recently, Villaécija-Aguilar and co-workers (2019) added that root traits like root hair development, root skewing, straightness, and diameter are regulated by KAR signaling, while both KAR and SL pathways contribute to the regulation of lateral root density and epidermal cell length. Furthermore, SLs have been implicated in plant stress responses to diverse abiotic factors (reviewed by Mostofa et al., 2018 ) like nutrient deficiency ( Kohlen et al., 2011 ), salinity and drought ( Ha et al., 2014 ; Wang et al., 2019 , reviewed by Mostofa et al., 2018 ) or chilling ( Cooper et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%